KEGIATAN HUMAS MELALUI WEBSITE TERHADAP PEMBENTUKAN CITRA PEMERINTAH KABUPATEN ACEH BARAT - Julian Elitear; Humaizi Humaizi; Dayana Dayana (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2021)
This study aims to analyze the information architecture, content,governance, website design, analyzing the image of West Aceh District Government,and to analyze how much the relationship of public relations activities through the website(website information architecture, website content, website governance, website design)towards the image formation of West Aceh District Government. Populationresearch is a website visitor acehbaratkab.go.id. Populationamounted to 261,943 people and by using Taro Yamane formula obtainedsample of 100 people. The technique of determining the sample using the methodpurposive sampling, and accidental sampling. Data collection of this studyusing questionnaires. The data collected is processed by usingcorrelation analysis to see the relationship of Public Relations Activities Through Websitewith the image of West Aceh District Government. The results foundthat the PR activities through the website of West Aceh which consists of architecturewebsite information shows good results, website content shows resultsthe less good, the website governance shows less good results, designthe website shows good results. The findings relate to the image of the Government of West Aceh of personality, reputation, value, corporate identity show average resultsnice.